Disturbance control in flexible manufacturing - Kuivanen, R. (International journal of human factors in manufacturing)
This article proposes that feedback from disturbances be used to redefine the system to overcome unwanted disturbances. This article describes the typical features of flexible manufacturing systems (FMS). A model and a classification is presented that explains the different orientations to disturbances and causes of disturbances based on a case study FMS in Finland.